Principal Leadership Management In Improving Teacher Professionalism At Ar-Risalah Bogor Integrated Islamic Junior High School - Novianti, Neneng; Rohmadi, Syamsul Huda (Pasundan Social Science Development, 2025)
This study aims to analyze the principal's leadership management in enhancing teacher professionalism at Ar-Risalah Integrated Islamic Junior High School, Bogor, for the 2023/2024 academic year. Teacher professionalism plays a critical role in determining the quality of education and student learning outcomes. As a school leader, the principal holds a vital responsibility in developing the competencies of teachers, which directly influences the overall teaching and learning environment. This research employs a qualitative descriptive approach, utilizing in-depth interviews with the school principal, teachers, and administrative staff to gain insights into leadership practices, supporting factors, and challenges related to teacher professional development. The findings indicate that the school principal's leadership management is instrumental in enhancing teacher professionalism through structured development programs such as in-house training, peer group discussions, and mentoring initiatives. These initiatives are tailored to address teachers’ needs and support continuous professional growth. However, the implementation faces several challenges, including time constraints due to additional workloads, limited financial resources, and the mismatch between training content and teachers' actual needs. Furthermore, the success of teacher development is significantly influenced by managerial support, collaborative culture among educators, and a positive school climate. This research concludes that effective leadership management is a key factor in driving teacher professional growth, which ultimately contributes to improved educational quality. The study provides relevant insights for school leaders and educational stakeholders in Islamic educational institutions seeking to foster teacher professionalism within a values-based and integrated curriculum framework.